ISLAMIC COUNSELING SERVICES IN THE FORMATION OF MENTAL HEALTH ACCORDING TO ZAKIAH DARADJAT - Dede Irma, Saiful Akhyar Lubis, Syamsu Nahar (Pascasarjana UIN Sumatera Utara, 2019)
Abstract: This study uses a qualitative approach to literature of the object. The purpose of thisstudy was to determine the concept, implementation and relevance of services for Islamic counselingin the formation of mental health according to Zakiah Daradjat. The results showed that:1) The concept of Islamic counseling services in the formation of mental health according toZakiah Daradjat basically needed help to overcome the difficulties it faced and various psychologicalservices emerged; and religion was the most important element in mental development. 2)Implementation of Islamic counseling services in the formation of mental health according toZakiah Daradjat is based on the principles of happiness of the world and the hereafter, principlesof communication and deliberation, principles of benefit, principles of compassion, principles ofhonor and respect, principles of security, principles of ta’awun or constructive cooperation, theprinciple of tolerance, the principle of justice. 3) The relevance of Islamic counseling services inthe formation of mental health departs from Islamic psychotherapy which has three regions, theyare: households (counselors in this area are parents and the value invested in mental establishmentis taqwa), school (the counselor is all agents schools with education in accordance with theteachings of religion), and the community (counselors in this area are individuals, especiallyleaders and rulers who provide counseling through policies made).Key Word: Islamic Counseling and Mental Health